Thermodynamic performance analysis of R-600 and R-600a as refrigerant - Ahamed, Jamal Uddin; Saidur, Rahman; Masjuki, Haji Hassan (University of Malaya, 2010)
In the developing countries like Malaysia, most of the vapor compression refrigeration system continues to run on halogenated refrigerants due to its excellent thermodynamic and thermo-physical properties. However, the halogenated refrigerants have adverse impacts such as ozone depletion potential and global warming potential. Hydrocarbons being natural fluid have drawn much attention of the scientists and researchers for the application as refrigerants. This paper presents a comparison of the energetic and exergetic performances of a domestic refrigerator using pure butane and isobutene as the refrigerant. The second law analysis such as exergy efficiency and exergy destruction, and coefficient of performance (COP) are investigated and were then compared with those of different refrigerants at varied operating conditions. Exergy efficiency of isobutene is found to be 50 higher than that of R-134a as a refrigerant mixture. The analyses show that the performances of butane and isobutene as refrigerants are comparable with HFC134a. It has also been found that at higher evaporating temperatures, the exergy losses are minimal for the refrigerants in the four components; the maximum exergy loss is occurred about 60 in the compressor.